Synergistic effect of land-use and vegetation greenness on vulture nestling body condition in arid ecosystems - Andrea Santangeli (Nature Portfolio, 2018)
Abstract Climate-driven environmental change and land-use change often interact in their impact on biodiversity, but these interactions have received little scientific attention. Here we study the effects of climate-driven environmental variation (i.e. vegetation greenness) and land-use (protected versus unprotected areas) on body condition of vulture nestlings in savannah landscapes. We combine ringing data on nestling measurements of two vultures (lappet-faced and African white-backed vulture) with land-use and environmental variables. We show that body condition of white-backed vulture nestlings decreased through the study period and was lowest inside protected areas. For the lappet-faced vulture, nestling condition was improved during harsh years with lower than average vegetation greenness assumed to result in increased ungulate mortality, but only within protected areas. Such interaction was not tested for the white-backed vulture due to collinearity. The species-specific effects of land-use and vegetation greenness on nestling condition of the two sympatric vulture species likely stem from their different life-histories, diet preferences and foraging behaviour. While translation of current findings on nestling conditions to their possible influence on population demography and species persistence require further studies, our findings demonstrate how environmental change may trigger selective bottom-up ecosystem responses in arid environments under global change.